Purification, characterization and application of cellulase from sewage sludge - Muna Tasnim Binti Mukhtaruddin (Kulliyyah of Engineering, International Islamic University Malaysia, 2011)
The production of cellulase from domestic sewage sludge could possibly bring an economic importance in certain industries as well as a key to solve the problem of environmental pollution. It could contribute to the alternative energy sources by applying the enzyme on the cellulosic materials from municipal and agricultural waste. Major bottleneck in the industrial applications is the high cost of the enzyme production and purification. Therefore, this study provided a way to enhance the recovery of the cellulase produced from sewage sludge by the separation and purification process. Purification using membrane was effective due to its less energy requirement and operational protocols. The results showed that separation by the membrane filtration using I kDa membrane size was found to be the best for the cellulase purification. It successfully increased the enzyme activity (CMCase) by 2.6 folds (17 U/ml to 45 U/ml). Characterization of the enzyme was carried out to evaluate the possible applications of the purified cellulase in industrial scale. A temperature of 50°C was found to be the optimum temperature for the stability of the enzyme. Besides, pH 3 showed the highest enzyme activity with the incubation time of 48 hours. The effluent generated during purification process of cellulase was characterized and found that it meets the mandatory standard set by the Department of Environment, Ministry of Natural Resources and Environment, Malaysia for the dischargeable to the water bodies or recycled process water. The results on the application of the enzyme to lignocellulosic biomasses indicated the considerable level of sugar production with optimum process conditions. In the application, waste paper and rice straw were used as the substrates. The results indicated that waste paper gave a better result in producing more glucose compared to rice straw. Therefore, waste paper has been chosen for the optimization of the process condition using Design Expert® 6.0.8 software. Two parameters i.e. enzyme dosage and substrate concentration were optimized. The optimum saccharification was achieved at 48 hr of incubation time with 5% substrate concentration and 15% enzyme dosage which gave 35.250 mg/ml of sugar or 70.5% saccharification. From the A[\/ OVA, 97.94% of the variables were best fitted for the model selected. The applications of cellulase on different substrates would not only provide key to manage the cellulosic waste disposal problem but also a way to convert the pollutant to alternative energy i.e. biofuels. Overall, the findings of this study prove that the cellulase enzyme obtained from the fermentation broth of sewage sludge shows high potential in the application of converting selected agricultural biomass into sugar (glucose) by developed saccharification process.